LIMITS OF THE POSTMODERN UNDERSTANDING OF IDENTITY - Honcharenko, Kateryna; Medved, Yurii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. Postmodern philosophy has redefined identity by deconstructing the centered subject, criticizing metanarratives, and rejecting ontological stability. These approaches provide tools for describing the fragmentation, fluidity, and contextual character of contemporary identity. However, the consistent implementation of this critical logic reveals a theoretical tension within postmodern thought itself. The aim of the article is to outline the limits of postmodern reflection on identity and to reveal the internal tension between the deconstruction of stable subjectivity and the observable continuity of the subject over time. The tasks include analyzing key postmodern strategies of problematizing identity, identifying their explanatory limits, and clarifying the conditions under which identity may persist without a fixed center. Research methods. The study is based on historical-philosophical and comparative analysis, as well as conceptual reconstruction. Research results. It is shown that postmodern approaches to identity successfully reveal the historical and conceptual limitations of the centered model of the subject, but do not fully explain the mechanisms of the subject’s temporal coherence. The analysis demonstrates that identity does not disappear under conditions of decentration but acquires a different mode of existence, characterized by continuity without a fixed center. In this way, the study identifies the internal analytical limit of postmodern thought in addressing the problem of identity. Discussion. The article provides a critical analysis of postmodern concepts of identity and interpretations of the subject’s continuity. It is shown that approaches focused on the deconstruction of the centered model of the “self” convincingly demonstrate the historical limitations of metaphysical stability, yet do not fully explain the mechanisms of the subject’s temporal coherence. This analysis allows for a refinement of the hypothesis that postmodernism does not abolish identity but rather shifts it into a different mode of existence. Conclusions. It is concluded that identity in conditions of deconstruction should not be understood as a return to metaphysical stability but as a mode of existence without a center. The problem shifts from restoring unity to conceptualizing continuity and responsibility under conditions of radical decentration. Thus, the limits of postmodern thought open new perspectives for reflection on identity.